An empirical investigation of the twin deficits hypothesis in Nigeria: Evidence from cointegration techniques - Nurudeen Abu; Awadh Ahmed Mohammed Gamal (Contemporary Economics, 2020)
Nigeria has not been able to generate adequate revenue to match her expenditure over the years. It is not surprising therefore, that the country frequently operates deficit budget with its negative consequences on the current account balance. This study investigates the twin deficits hypothesis (that is, budget deficits and current account deficits relationship) for Nigeria over the 1981-2017 period using the Autoregressive Distributed Lag (ARDL) and Dynamic Ordinary Least Squares (DOLS) estimation techniques. The result of the cointegration test indicates that there is a long-run relationship between budget deficits and current account deficits (along with oil prices and interest rate). The estimation results show that increases in budget deficits lead to increases in current account deficits in Nigeria in the short-run and the long-run. This finding validates the Keynesian assertion, but refutes the Ricardian Equivalence Hypothesis with respect to the relationship between the two deficits in Nigeria. The result of causality test using the Toda and Yamamoto (1995) approach illustrates the existence of a one-way causality from current account deficits to budget deficits. Based on this empirical evidence, this study recommends policies to reduce both deficits in Nigeria.
Keywords: E61; E62; F11; 330; Current account deficits; Budget deficits; Twin deficits; Cointegration techniques; Nigeria